The Effect of Work Quality, Work Environment on Employee Performance moderated Work Relationship Strategy - Fauziyah, Rizka; Rianto Rahadi, Dedi; Cheza Isyra Raisya, Athaya (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This study was conducted to observe the effect of work quality and work environment on employee performance moderated by work relationship strategies. The research method uses a quantitative approach using Smart-PLS 3 as a data processor and the object under study is company employees as many as 150 samples. Existing data is evaluated using relevant statistical analysis. The results of the study state if work quality, and work environment have an impact on employee performance moderated by the employment relationship strategy. The study results show that Work Quality has a significant effect on Employee Performance, Work Environment has no significant effect on Employee Performance, Work Relationship Strategy moderates the effect of Work Quality on Employee Performance, Work Relationship Strategy does not moderate the effect of Work Environment on Employee Performance, and Work Relationship Strategy has a significant effect on Employee Performance. Thus, it can be concluded that employee performance is not significantly influenced by the work environment and that the Work Relationship Strategy does not reduce how the workplace affects workers' performance. So companies can consider their work environment by providing a comfortable work environment